2002
DOI: 10.1177/1099636202004003140
|View full text |Cite
|
Sign up to set email alerts
|

Response of Syntactic Foam Core Sandwich Structured Composites to Three-Point Bending

Abstract: Use of syntactic foams as core materials gives several distinct advantages over traditionally used core materials. Syntactic foams have an excellent combination of compressive strength, low density, low radar detectability and low moisture absorption coefficient among others. The present work aims at studying the behavior of sandwich-structured composites containing syntactic foam as core material under three-point bending conditions. Flexural and short-beam shear tests are conducted, where large (16 : 1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 13 publications
0
32
0
3
Order By: Relevance
“…These properties have made them an attractive material for sandwich core applications. Many published studies on syntactic foam core sandwich composites examine their compression, bending and moisture absorption properties and affirm the suitability of such materials for aerospace and marine applications [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These properties have made them an attractive material for sandwich core applications. Many published studies on syntactic foam core sandwich composites examine their compression, bending and moisture absorption properties and affirm the suitability of such materials for aerospace and marine applications [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, these syntactic foams have found application as a core material in the construction of sandwich structures. [8,9] Summary: Syntactic foams containing 0.9, 1.76, 2.54, 3.54 and 4.5 vol.-% of E-glass fibres in the form of chopped strands were processed and subjected to three-point bending tests. The results showed that introduction of chopped strand fibres into the syntactic foam system increased the flexural strength.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on compressive properties of syntactic foams are several, [11,[14][15][16][17][18] but the investigations on flexural behaviour of syntactic foam core systems are scarce. [9,19] There are two new aspects in the present work. Firstly, while most of the works on syntactic foams were studied at low densities, the current work focuses on syntactic foams with higher densities in order to obtain better properties.…”
Section: Introductionmentioning
confidence: 99%
“…Syntactic foams are flexible and add new properties to these panels. Gupta et al [2] studied the behavior of sandwich-structured composites with syntactic foam core under three-point bending for both beams with large (16:1) and short (5:1) aspect ratio and gave a method to analyze failure of these structures. Gupta et al [3] studied the effect of microballoon radius ratio on the flexural properties of sandwich composites with syntactic foam core and their results show that in three and four point bending the radius ratio does not have any effect on the failure of the beam.…”
Section: Introductionmentioning
confidence: 99%